What Do Consumers’ Fund Flows Maximize? Evidence from Their Brokers’ Incentives - CHRISTOFFERSEN, SUSAN E. K.; EVANS, RICHARD; MUSTO, DAVID K. (Journal of Finance, 2013)
ABSTRACT We ask whether mutual funds’ flows reflect the incentives of the brokers intermediating them. The incentives we address are those revealed in statutory filings: the brokers’ shares of sales loads and other revenue, and their affiliation with the fund family. We find significant effects of these payments to brokers on funds’ inflows, particularly when the brokers are not affiliated. Tracking these investments forward, we find load sharing, but not revenue sharing, to predict poor performance, consistent with the different incentives these payments impart. We identify one benefit of captive brokerage, which is the recapture of redemptions elsewhere in the family.